2019
DOI: 10.1590/1806-3713/e20180138
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of and factors associated with asthma and wheezing in schoolchildren in Brazil

Abstract: Objective: To estimate the evolution of the prevalence of asthma and wheezing among schoolchildren in Brazil from 2012 to 2015, as well as to identify factors associated with both conditions. Methods: This was a cross-sectional study using data from the Brazilian National School-Based Adolescent Health Survey for 2012 and 2015. To characterize the evolution of the prevalence of asthma and wheezing, we used linear regression with weighted-least-squares estimation and presented the annual percent change (APC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…10 According to the 2012 Canadian Aboriginal Survey, the overall prevalence of lifetime asthma diagnosis was 16.0%. 11 A study of 50,991 people in China found that the overall prevalence of asthma was 4.2%, only 28.8% of asthma patients had been diagnosed, and 15.5% of asthma patients had visited the emergency room at least once. 12 Likewise, according to the results of three large-scale asthma surveys in China, the prevalence of asthma in childhood in China increased by nearly 50% every decade.…”
Section: Prevalence Of Asthmamentioning
confidence: 99%
“…10 According to the 2012 Canadian Aboriginal Survey, the overall prevalence of lifetime asthma diagnosis was 16.0%. 11 A study of 50,991 people in China found that the overall prevalence of asthma was 4.2%, only 28.8% of asthma patients had been diagnosed, and 15.5% of asthma patients had visited the emergency room at least once. 12 Likewise, according to the results of three large-scale asthma surveys in China, the prevalence of asthma in childhood in China increased by nearly 50% every decade.…”
Section: Prevalence Of Asthmamentioning
confidence: 99%
“…Entre as doenças respiratórias, a asma teve a maior taxa. Apesar de ser uma condição crônica, causada por fatores genéticos e ambientais, a APS tem importante papel no seu controle, uma vez que sua redução está relacionada a melhor acesso ao serviço médico e às medicações utilizadas para seu controle (20) . Sobre as pneumonias bacterianas é importante salientar que a diminuição de hospitalizações por essa condição está condicionada a uma melhor cobertura vacinal e ao incremento da vacina pneumocócica 10-valente no calendário vacinal, a partir de 2010, uma vez que pneumonia causada por Streptococcus pneumoniae é uma das principais causas de morbidade e mortalidade em crianças (21) .…”
Section: Tabela 3 Taxas De Internação Por Condições Sensíveis à Atenunclassified
“…10,[15][16][17][18] Among children, asthma is more prevalent in boys, but this changes in adolescence, with an increasing prevalence in girls. 7,19 Disease severity can be classified as persistent (41%), periodic (38%), or in remission (21%). 5 In 2015 the asthma prevalence in Brazil among 5-to 19-year-olds was 16%, while in 2020 there were an estimated 15,406 hospitalizations due to crises, costing a total of BRL 9,385,208.68.…”
Section: Introductionmentioning
confidence: 99%
“…20 Thus, asthma must be considered a public health problem, since it is responsible for many hospitalizations each year, whose expense impacts the health care system. 7,19,21,22 Diagnosis should be based on clinical findings. Symptoms and their inflammatory characteristics should be correlated with their frequency, as well as symptomatic response to specific medications.…”
Section: Introductionmentioning
confidence: 99%